2008
DOI: 10.1177/0032885508319208
|View full text |Cite
|
Sign up to set email alerts
|

Racial Desegregation in Prisons

Abstract: This article examines the history, law, and research on racial desegregation in American prisons. It focuses on the 2005 U.S. Supreme Court case of Johnson v. California, in which the Court held that prison administrators cannot racially segregate inmates unless under extraordinary circumstances to maintain the security of inmates, staff, and institutions. This article also examines evidence on attitudes and outcomes of racial desegregation in prisons. It ends with a discussion of racial desegregation mandates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…8 More specific to this study, group mean centering the level-2 predictors removed between-state variation in facility environments that could result from statelevel differences in racial segregation policies (see, for example, Trulson et al, 2008). Although we created a three-level data set in order to address all of these issues, it is important to understand that the models displayed here are technically two-level models because they only include measures at the first two levels of analysis (inmates and prisons).…”
Section: Discussionmentioning
confidence: 99%
“…8 More specific to this study, group mean centering the level-2 predictors removed between-state variation in facility environments that could result from statelevel differences in racial segregation policies (see, for example, Trulson et al, 2008). Although we created a three-level data set in order to address all of these issues, it is important to understand that the models displayed here are technically two-level models because they only include measures at the first two levels of analysis (inmates and prisons).…”
Section: Discussionmentioning
confidence: 99%
“…In response to federal court orders, both cellblocks and cells have to be integrated. This may serve to aggravate racial tensions (see Trulson, Marquart, Hemmens, & Carroll, 2008). Historically, the inherent racial tension between keepers and kept have been noted in prison studies (Carroll, 1974;Irwin, 1980;Marquart, 1986), paralleling the relationship found in free world studies involving police and citizens (Bayley & Mendelsohn, 1968;Scaglion & Condon, 1980).…”
Section: Characteristics Of Perpetratorsmentioning
confidence: 97%
“…A United States Supreme Court case (Johnson v. California 2005) revealed that correctional officials do not house inmates of different races in the same cell and segregate dormitory assignment (Trulson et al 2008). California prison gangs are racially homogenous groups, and the entire prison society runs both formally and informally along racial lines.…”
Section: Control Of Cellblocksmentioning
confidence: 99%